Double trouble: prevalence and factors associated with tuberculosis and diabetes comorbidity in Bangladesh - Sarker, Malabika; Barua, Mrittika; Guerra, Fiona; Saha, Avijit; Aftab, Afzal; Latif, A. H. M. Mahbub; Islam, Shayla; Islam, Akramul (BRAC Univeristy, 2018)
This article was published in the PLoS ONE [© 2016 PLoS ONE] and the definite version is available at : https://doi.org/10.1371/journal.pone.0165396 . The Journal's website is at: http://journals.plos.org/plosone/article?id=10.1371/journal.pone.0165396